Reconciliation provision under English and Malaysian family law: a comparative overview - Abdul Hak, Nora (Sweet & Maxwell Asia, 2008)
The principle of irretrievable breakdown of marriage is the basis of the law of divorce of Law Reform (Marriage and Divorce) Act 1976 (“LRA”) of Malaysia and Divorce Reform Act 1969/Matrimonial Causes Act 1973 (“MCA”) of England and Wales. In England and Wales, this is the sole ground for divorce. Malaysian law has, in addition, made conversion of one of the parties to Islam (s 51) and mutual consent (s 52) as grounds for divorce. Both jurisdictions emphasise the possibility of reconciliation between the spouses that may save the marriage. In England, the application of the provisions concerning reconciliation and conciliation under the MCA had faced difficulty since it came into force. This led to the reformation of the MCA into Family Law Act 1996 (“FLA”) especially provisions relating to the practice of reconciliation and conciliation, where mediation takes centre stage. The LRA however, remains the same today as it was introduced in 1976. Thus, the aim of this article is to review this aspect of the law, as the LRA of Malaysia is based, with some modifications, on the MCA of England. It is hoped that this article will highlight the strengths and weaknesses of the reconciliation provisions of both countries, i.e. Malaysia and England, with a view towards a better legal provision on reconciliation in the future.